Molecular characterization and differentiation of cucumber mosaic virus subgroups in Serbia by RT-PCR-RFLP - Zečević, Katarina; Stanković, Ivana; Petrović, Branka; Krstić, Branka (Archives of Biological Sciences, 2023)
Paper description: Restriction enzymes have been used in studies of the differentiation of cucumber mosaic virus (CMV) isolates but often only discriminating between virus subgroups I and II. This study provides the development and validation of RT-PCR-RFLP suitable for differentiating between CMV subgroups IA, IB and II. It describes a reliable and less costly protocol that allows for grouping CMV isolates into appropriate subgroups based on different genes. The protocol allows the analysis of many samples and first insight into the natural genetic population of CMV. Abstract: Samples of various host plants from different locations in Serbia showing foliar symptoms resembling those caused by the cucumber mosaic virus (CMV) were collected. Samples were considered CMV-infected after detection by double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA). Fifteen CMV isolates were selected for developing a reverse transcription-polymerase chain reaction (RT-PCR) restriction fragment length polymorphism (RFLP) protocol and a more detailed molecular characterization of all five genes. Based on in silico RFLP, the following restriction enzymes were selected: HindIII, SacII (1a gene), MluI (2a gene), StuI, SalI (2b gene), BaeI (movement protein (MP) gene of CMV), SfcI, and HaeIII (capsid protein (CP) gene), which were capable of distinguishing between subgroups of CMV based on the obtained characteristic restriction patterns. According to in situ RFLP, the predominant haplotype IA; IA, IA; IA, IA was determined in 14, while the distinct haplotype II; II, II; II, II was found in only one isolate. Sequence analyses of two selected Serbian CMV isolates with different restriction patterns and haplotype profiles confirmed the RFLP results, showing that isolates 674-11 and 137-13 belong to subgroups IA and II, respectively. Different restriction patterns after digestion of all five CMV genomic regions proved to be a simple way to investigate the natural population of CMV. This study provides insight into the genetic structure of the CMV population in Serbia.